Coordinating public debt and monetary management : institutional and operational arrangements - Dattels, Peter; Sundararajan, Vasudevan; Blommestein, H. J., 1950- (Washington, DC : International Monetary Fund, 1997)
This book examines issue and practices in the coordination of monetary and public debt management, drawing on the experience of both developing and advanced market economies, and argues that appropriete design and management of institutional and operating arrangements are important, particularly in economies liberalizing their financial systems.
Includes bibliographical references.
gau 23/06/14
Loans
Keywords: Monetary policy; Debts, Public; Debts, External